2008
DOI: 10.4088/jcp.v69n0806
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled 4-Week Study on the Efficacy and Safety of the Purinergic Agents Allopurinol and Dipyridamole Adjunctive to Lithium in Acute Bipolar Mania

Abstract: Objective The therapeutics for Bipolar Disorders (BD) is still far from adequate and new options with improved effectiveness, safety and tolerability in a wide range of patients are necessary. Preliminary data have suggested a role for dysfunctions targeting at the purinergic system in mood disorders. This study aimed to evaluate the efficacy and tolerability of the purinergic agents allopurinol and dipyridamole combined with lithium in bipolar mania. Method A randomized, placebo-controlled, double-blind stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 30 publications
5
89
1
6
Order By: Relevance
“…For example, we have demonstrated that allopurinol, a xanthine oxidase inhibitor, was an effective and well-tolerated adjuvant treatment for poorly responsive schizophrenia, refractory aggressive behavior and mania [125][126][127][128][129]. These results were confirmed by an independent group [130,131] and are hypothesized to be due to an indirect increase in extracellular purine levels (adenosine and guanosine) [12].…”
Section: Discussionsupporting
confidence: 68%
“…For example, we have demonstrated that allopurinol, a xanthine oxidase inhibitor, was an effective and well-tolerated adjuvant treatment for poorly responsive schizophrenia, refractory aggressive behavior and mania [125][126][127][128][129]. These results were confirmed by an independent group [130,131] and are hypothesized to be due to an indirect increase in extracellular purine levels (adenosine and guanosine) [12].…”
Section: Discussionsupporting
confidence: 68%
“…Two RCTs have now demonstrated the efficacy of adjunctive allopurinol for the treatment of acute mania (level 1) (70,71). In an eight-week RCT, allopurinol as adjunct to lithium plus haloperidol was found to be significantly more effective than placebo in 82 patients hospitalized with acute mania (70).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
“…In an eight-week RCT, allopurinol as adjunct to lithium plus haloperidol was found to be significantly more effective than placebo in 82 patients hospitalized with acute mania (70). In the second RCT (n = 180), comparing the addition of allopurinol, dipyridamole, or placebo to lithium for four weeks, allopurinol led to significantly greater improvements in mania scores and remission rates versus placebo (71). Although there is level 1 evidence for the use of allopurinol, given that it can cause hepatomegaly as well as hypersensitivity reactions such as Steven-Johnson syndrome and toxic epidermal necrolysis, it is recommended only for those patients that are refractory to other first-, second, and third-line treatments.…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 99%
“…A noção de suplementar o tratamento convencional com substân-cias que aliviem a sobrecarga oxidativa no transtorno bipolar é interessante e já foi investigada em ensaios clínicos 80,81 . A N-acetilcisteína (NAC) tem se mostrado um composto interessante nesse sentido.…”
Section: Estresse Oxidativounclassified